Isolation, Identification and Characterization of Gefitinib Novel Degradation Products by NMR and HRMS, Method Development and Validation by UPLC - Yanaka, Ramulu; Bindu Gandham, Hima; Swamy Rumalla, Chidananda; Kaliyaperumal, Muralidharan; John Saida, Shaik; Reddy Jammula, Abhinav (Asian Journal of Chemistry, 2021)
Gefitinib (GFT) sold under the brand name Iressa, is a medication used to treat certain type of breast, lung and other cancers, Gefitinib was subject to stress degradation under acidic, basic, peroxide mediated oxidation, photolytic and thermal degradation. The stress degradation was performed according to ICH guidelines Q1A(R2) and the drug was inert under thermal and photolytic conditions. One degradant is identified in acid hydrolysis referred as 7-methoxy-6-(3-morpholinopropoxy) quinazolin-4(3H)-one (GFT-DP1) and two degradants were formed in peroxide mediated hydrolysis referred as 4-(3-((4-((3-chloro-4-fluorophenyl)amino)-7-methoxy-1-oxidoquinazolin-6-yl)oxy)-propyl)morpholine-4-oxide (GFT-DP2) and 4-(3-((4-((3-chloro-4-fluorophenyl)amino)-7-methoxyquinazolin-6-yl)oxy)-propyl)-morpholine-4-oxide (GFT-DP3). In present study, all the novel three degradation product structures were confirmed by HRMS and 1D (1H, 13C) and 2D (COSY, HSQC and HMBC) based on 1D and 2D NMR data proton and carbon chemical shift values assigned exactly for all degradation products. A stability indicating RP-UPLC method was developed and validated with shorter run time and this method was validated in terms of linearity, specificity, accuracy, LOD and LOQ.